Fools, frauds and firebrands : thinkers of the new left - Scruton, Roger (Bloomsbury, 2015)
"In a previous book published in 1985 as 'Thinkers of the New Left,' [the author] brought together a series of articles from The Salisbury review. [He has] reworked the original articles, cutting out [some] writers, ... and including substantial new material devoted to developments that are increasingly influential"--Introduction.